Gene transfer may eradicate insect pests in sweet potato - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Sweet potato is one of the most important food crops in the developing world but it is susceptible to insect damage, which can cut its yield by up to 80%. New research may succeed in transferring a gene from cowpea which will help control the...